Adaptation of urban infill housing towards Malaysian City Centre revitalisation - 301891 Liew, Toh Yean (Skudai : Universiti Teknologi Malaysia, 2006)
Thesis (Sarjana Sains (Perancang Bandar dan Wilayah)) - Universiti Teknologi Malaysia, 2006